2011
DOI: 10.1103/physrevc.83.065802
|View full text |Cite
|
Sign up to set email alerts
|

Precise and accurate determination of theB8decay spectrum

Abstract: Accurate measurements of the 8 B neutrino spectrum are important for the interpretation of solar neutrino data. Experimentally, the 8 B neutrino spectrum can be obtained from the measurement of the β-delayed α spectrum. We report on an α-α coincidence measurement performed at the IGISOL facility in Jyväskylä, Finland. Our measurement allows extensive cross-checks to be performed and gives a more intense neutrino spectrum at high energies compared to the present standard. The deviation reaches 4% at the end poi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(4 citation statements)
references
References 58 publications
2
2
0
Order By: Relevance
“…Moreover, the 8 Bν e experimental spectrum agrees remarkably well with the theoretical prediction for neutrinos with an energy below 12 MeV. In particular, the 8 Bν e neutrino spectra deduced from four laboratory experiments [16,[18][19][20]100] agrees within about 1% at high neutrino energies, whereas before they differed by 4% [18]. Figure 1 shows Ψ e ⊙ (E ν ), the 8 Bν e spectrum emitted by the 8 B solar reaction in the Sun's core, with Ψ e ⊕ (E ν ) and Ψ µτ ⊕ (E ν ), the two components of the 8 Bν e neutrino spectrum measured on Earth.…”
Section: B Solar Electron-neutrino Spectrum and Flavor Oscillationssupporting
confidence: 79%
See 1 more Smart Citation
“…Moreover, the 8 Bν e experimental spectrum agrees remarkably well with the theoretical prediction for neutrinos with an energy below 12 MeV. In particular, the 8 Bν e neutrino spectra deduced from four laboratory experiments [16,[18][19][20]100] agrees within about 1% at high neutrino energies, whereas before they differed by 4% [18]. Figure 1 shows Ψ e ⊙ (E ν ), the 8 Bν e spectrum emitted by the 8 B solar reaction in the Sun's core, with Ψ e ⊕ (E ν ) and Ψ µτ ⊕ (E ν ), the two components of the 8 Bν e neutrino spectrum measured on Earth.…”
Section: B Solar Electron-neutrino Spectrum and Flavor Oscillationssupporting
confidence: 79%
“…The 8 Bν e spectrum emitted by the nuclear reactions in the Sun's core is identical to that determined by current laboratory experiments [e.g. [16][17][18][19][20]. Bahcall [21] has shown that the corrections on the shape of neutrino energy spectra caused by the surrounding plasma in the Sun's core are negligible.…”
Section: Introductionsupporting
confidence: 73%
“…The main aim of this experiment was to determine precisely the neutrino spectrum from the decay of 8 B through analysis of the beta-delayed alpha spectrum. The result of this part of the experiment along with a detailed description of the experimental procedures is described in [36,37]; the set-up consisted of four DSSSD detectors each backed by a thick Si detector in close geometry around the collection point. As a byproduct the high statistics of the experiment allowed to identify for the first time an electron capture branch in the decay of 8 B, namely to the 2 + 16.922 MeV state.…”
Section: The 8 B Experimentsmentioning
confidence: 99%
“…The 8 B neutrino spectrum measured in the laboratory agrees remarkably well with its theoretical prediction for neutrinos with an energy below 12 MeV, a small difference appearing only for high energy neutrinos. The experimental 8 B neutrino spectrum deduced from four laboratory experiments shows a difference with the theoretical prediction at most of 1% [62,[65][66][67][68]. Accordingly, we will consider that the electron neutrino energy spectrum of a solar nuclear reaction at the specific location where these neutrinos are created is identical to the equivalent neutrino spectrum measured in the laboratory.…”
Section: The Solar Electron Neutrino Spectramentioning
confidence: 94%